Law and other-spaces: legal geographies of the Sinai peninsula - Young, Tracy Allison (AUC Knowledge Fountain, 2013)
In recent years, Egypt’s Sinai Peninsula has joined an unfortunate category of what I call ‘Outlaw spaces’: spaces that are characterized and understood as being shaped by crisis, chaos and collapse. Outlaw spaces –which include the “black holes,” the “breeding grounds,” the “security vacuums” and the “no man’s lands” that have proliferated in the post-9/11 era—are constructed through the interplay of both legal and imaginative geographies. Mapping and labeling certain zones as lawless, chaotic and dangerous is deceptive. There is nothing natural about Outlaw spaces and it is not always clear where they begin and where they end. While Outlaw spaces are imagined as law-less, law may still be present – even abundant – in the space but works in strategic ways and along specific trajectories. Whether Outlaw spaces are dangerous, lawless, chaotic or not, the drawing of boundaries and labeling of the spaces they demarcate amounts to a forceful exercise of power and has important implications for the ways in which the space will be regulated, not regulated or selectively regulated through law. Conceiving a space to be outside the law not only creates truths about that space, it also seeks to provide an explanation for the nature of these spaces and in doing so, asserts the opposite qualities of in-law spaces that are constructed in their opposition. These processes of mapping, zoning, dividing and labeling of space are not just a tool for the use or non-use of law within a space, they also seek to provide a narrative for why the imperial eye of law has failed in its efforts to infinitely extend its reach to sanction and transform the Other. Rather than sanctioning, transforming or rebuilding Outlaw spaces, they may instead be simply contained, controlled, exploited or ignored.